Effectiveness of quranic murottal therapy on sleep quality improvement among stroke patients in clinical settings - Nurun Salaman Alhidayat; Bahtiar Yusuf; Zainab Zainab (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Stroke is a leading cause of disability and mortality worldwide and is frequently associated with sleep disturbances that may hinder recovery. Non-pharmacological interventions such as Qur’anic murottal therapy have been shown to induce relaxation and potentially improve sleep quality. This study aimed to examine the effect of Qur’anic murottal therapy on sleep quality among stroke patients at RSKD Dadi Makassar. Research Methodology: This study employed a pre-experimental design with a one-group pretest–posttest. A total of 37 respondents were selected through purposive sampling. The intervention consisted of listening to Qur’anic murottal therapy for three consecutive days. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test due to non-normal data distribution. Results: Before the intervention, all respondents (100%) had poor sleep quality. After the intervention, 86.5% of respondents demonstrated good sleep quality. The mean PSQI score decreased from 8.49±2.13 to 4.57±0.93. Statistical analysis showed a significant difference between pretest and posttest scores (p<0.001), indicating a meaningful improvement in sleep quality following the intervention. Conclusion: Qur’anic murottal therapy significantly improves sleep quality in stroke patients. This intervention can be recommended as a complementary nursing strategy to support holistic recovery in stroke care.